Effect of inner decoration coating on inner surface temperatures and heat flows under air-conditioning intermittent operation. (September 2019) - Meng, Xi; Du, Junfei; Gao, Yanna; Yu, Hanting
Abstract: Under air-conditioning intermittent operation, indoor air temperature varied sharply with air-conditioning operation behaviour and the much cool capacity was stored to form the cool load by wall materials close to the inner surface, especially for the inner decoration coating. To analyze the effect of the decoration coating on inner surface temperatures and heat flows, four typical walls with the different thermal insulation configurations were built with the different thermal properties of inner decoration coating, while the heat transfer model was established and verified by an experiment. Numerical simulation showed that the inner decoration coating had a significant influence on temperatures and heat flows in inner surface. The reduction of the density, the heat capacity or the heat conductivity coefficient of the decoration coating could obtain the improvement of the temperature response rate and the reduction of heat flow values. And in three studied thermal properties of inner decoration coating, the heat conductivity coefficient had the highest energy-saving efficiency.